Effects of Linseed Supplementation on Milk Production, Composition, Odd- and Branched-Chain Fatty Acids, and on Serum Biochemistry in Cilentana Grazing Goats - Nadia Musco; Raffaella Tudisco; Giulia Esposito; Piera Iommelli; Pajaree Totakul; Biagio D’Aniello; Pietro Lombardi; Ruggero Amato; Metha Wanapat; Federico Infascelli (Animals, 2022)
The purpose of this study was to investigate the effects of linseed supplementation on milk yield and quality, serum biochemistry and, in particular, to evaluate its possible effects on the production of odd- and branched-chain fatty acids (OBCFA) in the milk of Cilentana grazing goats. Twelve pregnant Cilentana dairy goats were divided into two groups (CTR, control, and LIN, linseed supplementation group). After kidding, the goats had free access to the pasture and both groups received a supplement of 400 g/head of concentrate, but the one administered to the LIN group was characterized by the addition of linseed (in a ratio of 20% as fed) to the ingredients. During the trial, milk samples were taken from April to August in order to evaluate milk production, composition, and fatty acid profile. In addition, blood samples were taken for evaluating the effects of linseed supplementation on goats’ health status. The health status of the goats was not influenced by the linseed supplementation, as confirmed by blood analyses. Concerning the effects on milk, the supplementation positively affected (p < 0.001) milk production and fat percentage and the fatty acid profile was markedly influenced by the lipid supplementation. In particular, milk from the LIN group was characterized by significantly lower concentrations of saturated fatty acids (FA; p < 0.001) and higher proportions of monounsaturated FA, polyunsaturated FA, and conjugated linoleic acids (CLAs) than milk from the CTR group (p < 0.001). In contrast, the OBCFA were negatively influenced by the linseed supplementation (p < 0.0001). Further studies are needed to test the effects of different fat sources and other nutrients on the diets.